Islamic Religious Education Teachers' Problems In Implementing The Independent Curriculum At Min 15 Pidie Jaya - Yuliani Yuliani; Dhiauddin Dhiauddin; Saifuddin Saifuddin (PT. Anagata Sembagi Education, 2025)
The phenomenon of the independent curriculum problem at MIN 15 Pidie Jaya has experienced several changes, especially the learning system. The Independent Curriculum (Kurmer) gives religious teachers more freedom in choosing and deciding on different teaching tools according to the needs and interests of their students. Based on the research context above, the author conducted a study with the research title